'Panda engagement' in China's digital public diplomacy. Issue 2 (3rd March 2020) - Huang, Zhao Alexandre; Wang, Rui
ABSTRACT: Applying a constructive journalistic paradigm, we examined how the Chinese media digitalized panda diplomacy on Twitter. By analyzing English-language, panda-themed tweets ( N  = 855) posted by Chinese state-owned media (Xinhua News Agency, People's Daily, and CGTN) in 2017, we identified content types and communication engagement practices that contributed to Chinese digital diplomacy. Our findings confirm that the practice of panda engagement online is highly politicized in the context of China's public diplomacy. Chinese media outlets use Twitter (a) to spread official discourse and views in the diplomatic arena to strengthen the government's impact and (b) to accrue sympathy capital and increase attractiveness through strategic placement of imagery (e.g. static images, moving gifs, and video clips) and textual narrative.